2017
DOI: 10.1021/acsnano.7b07698
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Third-Harmonic Generation in 2D Perovskites at Excitonic Resonances

Abstract: Two-dimensional hybrid organic-inorganic Ruddlesden-Popper perovskites (RPPs) have attracted considerable attention due to their rich photonic and optoelectronic properties. The natural multi-quantum-well structure of 2D RPPs has been predicted to exhibit a large third-order nonlinearity. However, nonlinear optical studies on 2D RPPs have previously been conducted only on bulk polycrystalline samples, in which only weak third-harmonic generation (THG) has been observed. Here, we perform parametric nonlinear op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(179 citation statements)
references
References 48 publications
(79 reference statements)
9
169
0
Order By: Relevance
“…also obtained (C 4 H 9 NH 3 ) 2 PbBr 4 (n=1), (C 4 H 9 NH 3 ) 2 PbI 4 (n=1), (C 4 H 9 NH 3 ) 2 (CH 3 NH 3 )Pb 2 I 7 (n=2), and (C 4 H 9 NH 3 ) 2 (CH 3 NH 3 ) 2 Pb 3 I 10 (n=3) (Figure b) through a STL method (for lead iodide R−P phases) or an AVC method (for lead bromide R−P phases). The THG emission intensity varies strongly with the thickness of the perovskite sheets due to signal depletion and phase‐matching conditions and the optimal thickness lies in the range of 22–61 nm for n=1 to 3 R‐P phases …”
Section: Crystal Structure Of Organic‐inorganic Perovskite Single Crymentioning
confidence: 58%
“…also obtained (C 4 H 9 NH 3 ) 2 PbBr 4 (n=1), (C 4 H 9 NH 3 ) 2 PbI 4 (n=1), (C 4 H 9 NH 3 ) 2 (CH 3 NH 3 )Pb 2 I 7 (n=2), and (C 4 H 9 NH 3 ) 2 (CH 3 NH 3 ) 2 Pb 3 I 10 (n=3) (Figure b) through a STL method (for lead iodide R−P phases) or an AVC method (for lead bromide R−P phases). The THG emission intensity varies strongly with the thickness of the perovskite sheets due to signal depletion and phase‐matching conditions and the optimal thickness lies in the range of 22–61 nm for n=1 to 3 R‐P phases …”
Section: Crystal Structure Of Organic‐inorganic Perovskite Single Crymentioning
confidence: 58%
“…Meanwhile, other optical properties, including third‐harmonic generation, parametric process, and stimulated Brillouin scattering, have been also explored, which promotes the development of layered materials‐based nonlinear optics.…”
Section: Fundamental Of 2d Layered Materialsmentioning
confidence: 99%
“…Feasibly, the weak van der Waals forces between the organic chains of adjacent layers, make it possible to exfoliate bulk 2D hybrid RPP crystals into thin sheets, which are interesting for both fundamental studies and potential applications. Indeed, it has recently been demonstrated that single‐crystalline butylammonium lead halide RPP nanosheets exhibit strong THG when pumping them with an IR laser at the three‐photon resonance of the 1s exciton . However, their NLO response under one‐photon‐resonant excitation has not yet been investigated.…”
Section: The Electronic (Eg) and Optical (Enormalgopt) Bandgaps Of Thmentioning
confidence: 99%
“…Five centimeter‐sized, pure phase RPP single crystals with the general formula [(BA) 2 (MA) n ‐1 Pb n X 3 n +1 ] (where BA = butylammonium (C 4 H 9 NH 3 ), MA = methylammonium (CH 3 NH 3 ), X = I − or Br − , and n is the number of inorganic layers within each quantum well) were synthesized through a temperature‐programmed crystallization method (for iodide‐based RPPs) or an antisolvent vapor diffusion method (for bromide‐based RPPs) . The synthesized crystals are [(BA) 2 PbBr 4 ] ( n = 1), [(BA) 2 PbI 4 ] ( n = 1), [(BA) 2 (MA)Pb 2 I 7 ] ( n = 2), [(BA) 2 (MA) 2 Pb 3 I 10 ] ( n = 3), and [(BA) 2 (MA) 3 Pb 4 I 13 ] ( n = 4), hereafter denoted as Br n =1 , I n =1 , I n =2 , I n =3 , and I n =4 , respectively.…”
Section: The Electronic (Eg) and Optical (Enormalgopt) Bandgaps Of Thmentioning
confidence: 99%